Prevalence of stunting, wasting and underweight in Grade 1-learners: The NW-CHILD Study - Gizelle Kruger; Anita E. Pienaar; Dané Coetzee; Salomé H. Kruger (AOSIS, 2014)
Background: Child undernutrition remains a major public health concern in developing countries, with many negative consequences to child development. Objectives: To determine the prevalence of stunting, wasting and underweight amongst Grade 1-learners in the North West Province (NWP) of South Africa (SA), taking into account gender, race and school type. Method: Eight hundred and sixteen (419 boys, 397 girls) learners participated in the study (567 black, 218 white, 31 other races). Underweight, stunting and wasting (Weight-for-age, height-for-age, BMI-for-age) were determined using the z-scores of the 2007 WHO reference sample (-2 SD). Results: A higher prevalence of wasting and underweight were found amongst the boys (8.35%; 5.97%) compared with the girls (6.30%; 2.52%), although this was only significant for underweight (p = 0.02), whilst stunting percentages were very similar amongst girls (4.53%) and boys (4.06%). Underweight was the highest in the black group (5.47%; p< 0.01), compared with the white group (0.46%) and the prevalence of the conditions is associated with school types which represent low socio-economic circumstances (Quintile 1-3 schools). Only black learners showed stunting (p< 0.01) and more black learners were wasted (n= 39) compared with white (n= 15; p= 0.08) learners. Quintile 1-3 schools had a significantly higher prevalence of underweight (5.14%- 8.18%) and stunting (3.88%- 10.7%) (p< 0.01) compared with Quintile 4 and 5 schools. Conclusion: The prevalence of stunting, wasting and underweight need improvement amongst school beginners, especially in Quintile 1-3 type schools but also amongst black learners living in the NWP of SA as it can have significant hampering effects on the future development and well-being of children.